2023
DOI: 10.1186/s43093-023-00190-8
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of mobile commerce adoption intention by Saudi SMEs during the COVID-19 pandemic

Abstract: Grounded in the technology-organization-environment framework, this paper investigates critical drivers of mobile commerce (m-commerce) adoption intention by SMEs in Saudi Arabia, a developing country in transition, during the COVID-19 pandemic. A quantitative approach was adopted in this study for data collection and analysis. A proposed research model was tested and validated using PLS-SEM on data collected using a structured questionnaire from a sample of 171 Saudi SMEs located in the capital city of Riyadh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
0
0
Order By: Relevance
“…Furthermore, the results revealed that relative advantages, IT experience, top management support, IT knowledge from the management teams, and external pressure have a significant impact on the adoption of electronic marketing. Additionally, some research has discovered that management support is one of the most important elements that foster the intention to adopt mobile commerce [17], [18], the adoption of blockchain [19], as well as the adoption of big data [20].…”
mentioning
confidence: 99%
“…Furthermore, the results revealed that relative advantages, IT experience, top management support, IT knowledge from the management teams, and external pressure have a significant impact on the adoption of electronic marketing. Additionally, some research has discovered that management support is one of the most important elements that foster the intention to adopt mobile commerce [17], [18], the adoption of blockchain [19], as well as the adoption of big data [20].…”
mentioning
confidence: 99%
“…Saudi Arabia, which is one of the G20 countries, has a well-developed IT infrastructure (Alaskar, 2023), and deep (digital) transformations are underway in line with the Saudi 2030 Vision launched in 2016 (Alaskar & Alsadi, 2023). The country's considerable achievements in digital transformation enabled it to make a remarkable progress according to global indicators (Saudi Vision 2030).…”
mentioning
confidence: 99%
“…In this study, we address the research gap and contribute to the literature on DPC, FA, NC, and FP in three ways. First, this paper seeks to access the links among DPC, FA, NC, and FP in the Saudi context, an emerging country with a fast-growing economy, robust digitalization strategy, and fairly developed digital infrastructure (Alaskar & Alsadi, 2023). Such research helps to increase understanding of the influence mechanisms of DPC in relation to other mediating and dependent variables when relying on a parallel mediation model and data collected from 422 Saudi firms.…”
mentioning
confidence: 99%